Characterization of N-Acyl Phosphatidylethanolamine-Specific Phospholipase-D Isoforms in the Nematode Caenorhabditis elegans - Harrison, Neale; Lone, Museer A.; Kaul, Tiffany K.; Reis Rodrigues, Pedro; Ogungbe, Ifedayo Victor; Gill, Matthew S. (PLOS ONE, 2014)
N-acylethanolamines are an important class of lipid signaling molecules found in many species, including the nematode Caenorhabditis elegans (C. elegans) where they are involved in development and adult lifespan. In mammals, the relative activity of the biosynthetic enzyme N-acyl phosphatidylethanolamine-specific phospholipase-D and the hydrolytic enzyme fatty acid amide hydrolase determine N-acylethanolamine levels. C. elegans has two N-acyl phosphatidylethanolamine-specific phospholipase-D orthologs, nape-1 and nape-2, that are likely to have arisen from a gene duplication event. Here, we find that recombinant C. elegans NAPE-1 and NAPE-2 are capable of generating N-acylethanolamines in vitro, confirming their functional conservation. In vivo, they exhibit overlapping expression in the pharynx and the nervous system, but are also expressed discretely in these and other tissues, suggesting divergent roles. Indeed, nape-1 over-expression results in delayed growth and shortened lifespan only at 25°C, while nape-2 over-expression results in significant larval arrest and increased adult lifespan at 15°C. Interestingly, deletion of the N-acylethanolamine degradation enzyme faah-1 exacerbates nape-1 over-expression phenotypes, but suppresses the larval arrest phenotype of nape-2 over-expression, suggesting that faah-1 is coupled to nape-2, but not nape-1, in a negative feedback loop. We also find that over-expression of either nape-1 or nape-2 significantly enhances recovery from the dauer larval stage in the insulin signaling mutant daf-2(e1368), but only nape-1 over-expression reduces daf-2 adult lifespan, consistent with increased levels of the N-acylethanolamine eicosapentaenoyl ethanolamine. These results provide evidence that N-acylethanolamine biosynthetic enzymes in C. elegans have conserved function and suggest a temperature-dependent, functional divergence between the two isoforms.